Recurrence Within 24 Hours of Unprovoked Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The incidence and risk factors of acute recurrence of unprovoked seizures within 24 hours of admission to an Emergency Department (ED) were analyzed by a retrospective chart review at Schneider Children's Hospital, New York.